Supporting educational loan decision making using neural network - Yusoff, Nooraini; Siraj, Fadzilah (Faculty of Information Technology, Universiti Utara Malaysia, 2006)
This study introduces i-Neuro, a decision support system that can assist in loan decision making by educational loan funding institutions. i-Neuro is a predictive system that integrates Neural Network technique, thus can help the management to predict which application to accept or reject. The prediction can be done as Neural Network has trained previous batch of loan application data and stored association between application characteristics (attributes) that explains which applications were accepted and rejected. The association in previous data can predict the new current application. The use of i-Neuro in loan application processing reduces the management workload by providing the list of eligible applicants based on the merit agreed by the management. As a result, the time required for loan application processing can be reduced as well as allowing the management to update the information in database easily. i-Neuro system has been tested on real data. It has shown to achieve satisfactory results and indicates its potential in facilitating the loan application processing.